Changes in Consumer Preferences toward Non‐GM Foods within an Information‐Rich Environment: The Case of the Washington State Ballot Initiative. Issue 1 (8th December 2020) - Magnier, Alexandre; Kalaitzandonakes, Nicholas; Lusk, Jayson
Abstract: In this study, we investigate the impact of information on consumer preference for GM foods. In November 2013, the state of Washington voted on ballot initiative I‐522, which would have required the labeling of GM foods. The political campaign preceding the vote gave rise to an information‐rich environment where positive and negative information about GM foods became available to consumers in this state. We estimated the WTP for avoiding GM ingredients before and at the time of the vote and found that the WTP for non‐GM foods declined. This result is consistent with the proposition that information can affect consumer preferences for GM foods.